If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 136 + -3x = 33x + 20 Reorder the terms: 136 + -3x = 20 + 33x Solving 136 + -3x = 20 + 33x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33x' to each side of the equation. 136 + -3x + -33x = 20 + 33x + -33x Combine like terms: -3x + -33x = -36x 136 + -36x = 20 + 33x + -33x Combine like terms: 33x + -33x = 0 136 + -36x = 20 + 0 136 + -36x = 20 Add '-136' to each side of the equation. 136 + -136 + -36x = 20 + -136 Combine like terms: 136 + -136 = 0 0 + -36x = 20 + -136 -36x = 20 + -136 Combine like terms: 20 + -136 = -116 -36x = -116 Divide each side by '-36'. x = 3.222222222 Simplifying x = 3.222222222
| 4x-5=80 | | 24=3(x+1)-3 | | 7x-27=4x+12 | | 7t^2+4t=5 | | 4T/3=T+20 | | 8*x^2+1000=0 | | 10h+2+4h-6=-16 | | 3x^2-4x^3=0 | | 3x=4x^2 | | 13-7x=113-35x | | -10=y | | 2/5(x+23)=8 | | 4(a+b)=b-a+2x | | 6x+5=8x-1 | | 3x^2-5x^2-9x+15=0 | | x-4=24-12 | | 40=29+1/3x | | 2/3x+15 | | 12x+5=x+25 | | 4w^2+5w+6=0 | | 6a+3(1c+3)=0 | | 1/3q=18 | | 6x*-13x+5=0 | | m(x+n)=n | | 5x-25=5+6x | | -16(2x-8)-(18x-6)=-12+2(6x-6) | | 30-(x+9)=8x-6 | | 27-x=8x | | 8x+10-2x=12+6x-2 | | 26-4x=9-9x | | (z-5)(z-7)=0 | | 5x-5=2x+97 |